Indie State: Fanzine Indie - Broncano Ramirez, Sofia Noely (2024)
The project consists of the creation of a digital fanzine that publicizes the current Lima indie musical scene, compiles information about the places and environments in which this scene takes place, illustrates the behavior of the actors involved and identifies the key moments in its development. The project is based on the idea of generating a means of communication to obtain a record of the Lima indie scene. With the emergence of new movements and forms of musical expression, it is important to document and publicize this emerging scene. To do this, a fanzine is used that brings together photography and design, and that will function as a means to show the current state of the Lima indie scene. The purpose of this project is to generate sensations, transmit emotions and show the essence of this musical genre through images.